2017
DOI: 10.1002/term.2595
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysate activates quiescent cell proliferation and reprogramming in human articular cartilage: Involvement of hypoxia inducible factor 1

Abstract: The idea of rescuing the body self-repair capability lost during evolution is progressively gaining ground in regenerative medicine. In particular, growth factors and bioactive molecules derived from activated platelets emerged as promising therapeutic agents acting as trigger for repair of tissue lesions and restoration of tissue functions. Aim of this study was to assess the potential of a platelet lysate (PL) for human articular cartilage repair considering its activity on progenitor cells and differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…In this study, the proliferative trend demonstrated by doubling number and cyclin D1 protein levels were markedly higher in ACs-PL compared to ACs-FBS and similar between ACs-PL and CPCs-PL. These results are in accordance with previous works, where PL treatment on partially growth-arrested chondrocytes is reported as responsible for their cell cycle re-entry and strong mitogenic response [14,30]. Moreover, we further showed that the increase in proliferation is concomitant with a senescence attenuation in ACs-PL, at a similar level to that of CPCs-PL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the proliferative trend demonstrated by doubling number and cyclin D1 protein levels were markedly higher in ACs-PL compared to ACs-FBS and similar between ACs-PL and CPCs-PL. These results are in accordance with previous works, where PL treatment on partially growth-arrested chondrocytes is reported as responsible for their cell cycle re-entry and strong mitogenic response [14,30]. Moreover, we further showed that the increase in proliferation is concomitant with a senescence attenuation in ACs-PL, at a similar level to that of CPCs-PL.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the high content in mitogenic growth factors, platelet products exert a strong proliferative stimulus on several in vitro cell cultures, as previously reported [14,15,30]. In this study, the proliferative trend demonstrated by doubling number and cyclin D1 protein levels were markedly higher in ACs-PL compared to ACs-FBS and similar between ACs-PL and CPCs-PL.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Subsequently, HIF-1α regulates mitochrodrial apoptotic pathway-relevant proapoptotic proteins (Bcl-2 and Bcl-xl) expression and thereby activates caspase family to induce cell apoptosis (Liu, Ai, Feng, Li, & Liu, 2016). In addition, HIF-1α also exhibits a tight link with the cell proliferation (Nguyen, Cancedda, & Descalzi, 2017). As shown in the current study (Supporting Information Figures S1, 1, and 2), HIF-1α expression levels and cell apoptosis of ACL fibroblasts were significantly increased by severe hypoxic environmental conditions, which would lead to the reduction of the number of ACL fibroblasts.…”
mentioning
confidence: 99%
“…Moreover, it was demonstrated chondroitin sulfate, an important molecule in cartilage extracellular matrix, improved chondrogenesis of MSCs [43]. Besides, Nguyen et al, demonstrated that PL induces reprograming of quiescent cartilage cells resulted in new cartilage formation [91] The expression of Coll X along with MMP-13 is typically expressed in the hypertrophy pathway.…”
Section: Discussionmentioning
confidence: 99%